(untitled) (FULafia Journal of Science and Technology, 2018)
This study evaluated blood samples of 150 adults of age range 30-79 years with 96 males and 54 females on immunology indices; malondialdehyde (MDA), immunoglobin M (IgM) and cluster of differentiation 4 (CD+ 4). Serum MDA concentration significantly (p<0.05) increased with age. Serum MDA concentration of the males were significantly higher than the females. It indicates that the healthy ageing adult’s antioxidant/oxidant balance is compromised. Thus, the generation of reactive oxygen species (ROS) and ROS clearance has been disturbed and may result in oxidative damage to macromolecules in the cells. In all ages and gender, IgM antibodies to H. pylori was significantly (p<0.05) different and it increased with age. Study showed that IgM antibodies to H. Pylori was significantly (p<0,05) higher in males than females, thus higher level in elderly indicates an increase in autoimmune disease activity